RLEP LAMP for the laboratory confirmation of leprosy: towards a point-of-care test - Malkin Saar (BMC, 2021)
Abstract Background Nucleic acid-based amplification tests (NAAT), above all (q)PCR, have been applied for the detection of Mycobacterium leprae in leprosy cases and household contacts with subclinical infection. However, their application in the field poses a range of technical challenges. Loop-mediated isothermal amplification (LAMP), as a promising point-of-care NAAT does not require sophisticated laboratory equipment, is easy to perform, and is applicable for decentralized diagnosis at the primary health care level. Among a range of gene targets, the M. leprae specific repetitive element RLEP is regarded as highly sensitive and specific for diagnostic applications.  Methods Our group developed and validated a dry-reagent-based (DRB) RLEP LAMP, provided product specifications for customization of a ready-to-use kit (intended for commercial production) and compared it against the in-house prototype. The assays were optimized for application on a Genie® III portable fluorometer. For technical validation, 40 “must not detect RLEP” samples derived from RLEP qPCR negative exposed and non-exposed individuals, as well as from patients with other conditions and a set of closely related mycobacterial cultures, were tested together with 25 “must detect RLEP” samples derived from qPCR confirmed leprosy patients. For clinical validation, 150 RLEP qPCR tested samples were analyzed, consisting of the following categories: high-positive samples of multibacillary (MB) leprosy patients (> 10.000 bacilli/extract), medium-positive samples of MB leprosy patients (1.001–10.000 bacilli/extract), low-positive samples of MB leprosy patients (1–1.000 bacilli/extract), endemic controls and healthy non-exposed controls; each n = 30.  Results Technical validation: both LAMP formats had a limit of detection of 1.000 RLEP copies, i.e. 43–27 bacilli, a sensitivity of 92% (in-house protocol)/100% (ready-to-use protocol) and a specificity of 100%. Reagents were stable for at least 1 year at 22 °C. Clinical validation: Both formats showed a negativity rate of 100% and a positivity rate of 100% for high-positive samples and 93–100% for medium positive samples, together with a positive predictive value of 100% and semi-quantitative results. The positivity rate for low-positive samples was 77% (in-house protocol)/43% (ready-to-use protocol) and differed significantly between both formats.  Conclusions The ready-to-use RLEP DRB LAMP assay constitutes an ASSURED test ready for field-based evaluation trials aiming for routine diagnosis of leprosy at the primary health care level.